Controlled Fabrication of Bioactive Microtubes for Screening Anti-Tongue Squamous Cell Migration Drugs - Tang, Rongbing; Yang, Lu; Shen, Liheng; Ma, Xuan; Gao, Yinfeng; Liu, Yuan; Bai, Zhen; Wang, Xuemei (Frontiers in Chemistry, 2022)
The treatment of tongue squamous cell carcinoma (TSCC) faces challenges because TSCC has an aggressive biological behavior and manifests usually as widespread metastatic disease. Therefore, it is particularly important to screen out and develop drugs that inhibit tumor invasion and metastasis. Two-dimensional (2D) cell culture has been used as in vitro models to study cellular biological behavior, but growing evidence now shows that the 2D systems can result in cell bioactivities that deviate appreciably the in vivo response. It is urgent to develop a novel 3D cell migration model in vitro to simulate the tumor microenvironment as much as possible and screen out effective anti-migration drugs. Sodium alginate, has a widely used cell encapsulation material, as significant advantages. We have designed a microfluidic device to fabricate a hollow alginate hydrogel microtube model. Based on the difference in liquid flow rate, TSCC cells (Cal27) were able to be evenly distributed in the hollow microtubes, which was confirmed though fluorescence microscope and laser scanning confocal microscope (LSCM). Our microfluidic device was cheap, and commercially available and could be assembled in a modular way, which are composed of a coaxial needle, silicone hose, and syringes. It was proved that the cells grow well in artificial microtubes with extracellular matrix (ECM) proteins by LSCM and flow cytometry. Periodic motility conferred a different motor state to the cells in the microtubes, more closely resembling the environment in vivo. The quantitative analysis of tumor cell migration could be achieved simply by determining the position of the cell in the microtube cross-section. We verified the anti-migration effects of three NSAIDs drugs (aspirin, indomethacin, and nimesulide) with artificial microtubes, obtaining the same results as conventional migration experiments. The results showed that among the three NSAIDs, nimesulide showed great anti-migration potential against TSCC cells. Our method holds great potential for application in the more efficient screening of anti-migration tumor drugs.